Museum of thieves ebook - Tanner, Lian (The Keepers Trilogy, 2010)
Welcome to the tyrannical city of Jewel, where impatience is a sin and boldness is a crime. Goldie Roth has lived in Jewel all her life. Like every child in the city, she wears a silver guardchain and is forced to obey the dreaded Blessed Guardians. She has never done anything by herself and won’t be allowed out on the streets unchained until Separation Day. When Separation Day is canceled, Goldie, who has always been both impatient and bold, runs away, risking not only her own life but also the lives of those she has left behind. In the chaos that follows, she is lured to the mysterious Museum of Dunt, where she meets the boy Toadspit and discovers terrible secrets. Only the cunning mind of a thief can understand the museum’s strange, shifting rooms. Fortunately, Goldie has a talent for thieving. Which is just as well, because the leader of the Blessed Guardians has his own plans for the museum—plans that threaten the lives of everyone Goldie loves. And it will take a daring thief to stop him. . . . Museum of Thieves is a thrilling tale of destiny and danger, and of a courageous girl who has never been allowed to grow up—until now.